Effects of Combined Oxytocin and Beta-3 Receptor Agonist (CL 316243) Treatment on Body Weight and Adiposity in Male Diet-Induced Obese Rats - Edwards, Melise M.; Nguyen, Ha K.; Dodson, Andrew D.; Herbertson, Adam J.; Wietecha, Tomasz A.; Wolden-Hanson, Tami; Graham, James L.; Honeycutt, Mackenzie K.; Slattery, Jared D.; O’Brien, Kevin D.; Havel, Peter J.; Blevins, James E. (Frontiers in Physiology, 2021)
Previous studies have indicated that oxytocin (OT) reduces body weight in diet-induced obese (DIO) rodents through reductions in energy intake and increases in energy expenditure. We recently demonstrated that hindbrain [fourth ventricular (4V)] administration of OT evokes weight loss and elevates interscapular brown adipose tissue temperature (TIBAT) in DIO rats. What remains unclear is whether OT can be used as an adjunct with other drugs that directly target beta-3 receptors in IBAT to promote BAT thermogenesis and reduce body weight in DIO rats. We hypothesized that the combined treatment of OT and the beta-3 agonist, CL 316243, would produce an additive effect to decrease body weight and adiposity in DIO rats by reducing energy intake and increasing BAT thermogenesis. We assessed the effects of 4V infusions of OT (16 nmol/day) or vehicle (VEH) in combination with daily intraperitoneal injections of CL 316243 (0.5 mg/kg) or VEH on food intake, TIBAT, body weight and body composition. OT and CL 316243 alone reduced body weight by 7.8 ± 1.3% (P < 0.05) and 9.1 ± 2.1% (P < 0.05), respectively, but the combined treatment produced more pronounced weight loss (15.5 ± 1.2%; P < 0.05) than either treatment alone. These effects were associated with decreased adiposity, adipocyte size, energy intake and increased uncoupling protein 1 (UCP-1) content in epididymal white adipose tissue (EWAT) (P < 0.05). In addition, CL 316243 alone (P < 0.05) and in combination with OT (P < 0.05) elevated TIBAT and IBAT UCP-1 content and IBAT thermogenic gene expression. These findings are consistent with the hypothesis that the combined treatment of OT and the beta-3 agonist, CL 316243, produces an additive effect to decrease body weight. The findings from the current study suggest that the effects of the combined treatment on energy intake, fat mass, adipocyte size and browning of EWAT were not additive and appear to be driven, in part, by transient changes in energy intake in response to OT or CL 316243 alone as well as CL 316243-elicited reduction of fat mass and adipocyte size and induction of browning of EWAT.